11. Diagnostic surra (Trypanosoma evansi) on Buffalo Slaughtered in Banda Aceh and Aceh Besar Slaughterhouses Based on Card Agglutination Test for Trypanosoma evansi (CATT) - Farida Athaillah; kartika Amira; Yudha Fahrimal (Universitas Syiah Kuala, 2021)
This study aims to detect the presence of parasites indirectly by looking at antibodies to Trypanosoma evansi by using the method of Card Agglutination Test for Trypanosoma evansi (CATT). A total of 50 heads of buffaloes cut at Banda Aceh and Aceh Besar Slaughterhouses were taken blood for examination at the Parasitology and Research Laboratory of the Faculty of Veterinary Medicine of Syiah Kuala University. The principle of the CATT method is to look at the bonds between antibodies and antigens. Positive results are characterized by the formation of agglutination on the CATT paperboard. The score of agglutination reactions is divided into 5 categories, positive triple (+++) indicates agglutination is very strong, which means the possibility of newly infected animals, positive two (++) signifies strong agglutination, which means the animal may have been infected long enough, one (+) denotes moderate agglutination, meaning the animal has already been infected with T. evansi, dubious (±) denotes weak or dubious agglutination and, negative (-) signifies no agglutination. The results showed that from 50 samples examined, 14% (7/50) positive samples of agglutination were very strong, 24% (12/50) positive samples of strong agglutination, 48% (24/50) positive samples of moderate agglutination, and 0 negative samples T. evansi. The CATT method is very sensitive because 86% of the 50 buffaloes are tested positive or infected with T. evansi.